1999
DOI: 10.1136/thx.54.5.390
|View full text |Cite
|
Sign up to set email alerts
|

Lung and chest wall mechanics in ventilated patients with end stage idiopathic pulmonary fibrosis

Abstract: Background-Idiopathic pulmonary fibrosis is an inflammatory disease which leads to chronic ventilatory insuYciency and is characterised by a reduction in pulmonary static and dynamic volumes. It has been suggested that lung elastance may also be abnormally increased, particularly in end stage disease, but this has not been systematically tested. The aim of this study was to assess the respiratory mechanics during mechanical ventilation in patients aVected by end stage disease. Methods-Respiratory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
86
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 28 publications
8
86
0
6
Order By: Relevance
“…22 Fernández-Pérez and co-workers also showed a poor outcome with high PEEP, as it may overinflate relatively intact lung units. It also has no effect on fibrotic, unrecruitable regions, and thus promotes ventilator interaction lung injury in patients with ILDs.…”
Section: Discussionmentioning
confidence: 97%
“…22 Fernández-Pérez and co-workers also showed a poor outcome with high PEEP, as it may overinflate relatively intact lung units. It also has no effect on fibrotic, unrecruitable regions, and thus promotes ventilator interaction lung injury in patients with ILDs.…”
Section: Discussionmentioning
confidence: 97%
“…A study of seven patients with IPF receiving mechanical ventilation found that the elastance and the resistance of the respiratory system was markedly increased and correlated with the degree of hypercapnia. These phenomena may contribute to the observed absence of respiratory improvement in this patient group [36].…”
Section: Ventilationmentioning
confidence: 82%
“…In the period 1980-2000, a group of studies highlighted the inadequacy of mechanical ventilation in acute respiratory failure in IPF. Pooled data showed an aggregated mortality of 87% (118 out of 135), and short-term mortality (within 3 months of hospital discharge) of 94% [27,[32][33][34][35][36][37][38]. A study of seven patients with IPF receiving mechanical ventilation found that the elastance and the resistance of the respiratory system was markedly increased and correlated with the degree of hypercapnia.…”
Section: Ventilationmentioning
confidence: 99%
“…Some studies also discuss the importance of these measures in patients with pulmonar fibrosis (21) or with the human immunodeficiency virus (HIV) and pneumonia (22).…”
Section: Resultsmentioning
confidence: 99%
“…In pulmonary fibrosis, the low (C RS ) is associated with hypoventilation and hypercapnia (21,26). In individuals with HIV and pneumonia, changes in lung mechanics are similar to patients with ARDS, i.e., low (C RS ) and (C RS ) (22).…”
Section: Resultsmentioning
confidence: 99%